Policing Domestic Abuse : risk, policy and practice - Barrow-Grint, Katy; Sebire, Jacqueline; Turton, Jackie (London & New York: Routledge, 2023)
"This book is dedicated to improving the practice of the policing of Domestic Abuse. Its objective is to help inform those working in policing about the dynamics of how domestic abuse occurs, how best to respond to and investigate it and in the longer term how to prevent it. Divided into thematic areas, the book uses recent research findings to update some of the theoretical analysis and to highlight areas of good practice: 'what works and why'. Effective investigation and the prosecution of offenders is considered as well as an evaluation of the success of current treatment options. Policing domestic abuse can only be dealt with through an effective partnership response. The responsibilities of each agency and the statutory processes in place when policy is not adhered to are outlined. Core content includes: A critique of definitions and theoretical approaches to domestic abuse, including coverage of the myths surrounding domestic abuse and their impact on policing; An exploration on the challenges of collecting data on domestic abuse, looking at police data and the role of health and victim support services; A critical review of different forms of abuse, different perpetrators and victims and risk assessment tools used by the police; A critical examination of the law relating to domestic abuse, how police resources are deployed to respond to and manage it, and best practice in investigation, gathering evidence and prosecution. Key perspectives on preventing domestic abuse, protecting victims and harm reduction. Written with the student and budding practitioner in mind, this book is filled with case studies, current research, reports and media examples, as well as a variety of reflective questions and a glossary of key terms, to help shed light on the challenges of policing domestic violence and the links between academic research and best practice"--
Includes bibliographical references and index.
Keywords: Family violence -- Prevention; Police